Genetic analyses identify circulating genes related to brain structures associated with Parkinson’s disease - Zhe Han; Yanping Zhu; Zhenhong Xia; Qing Deng; Hongjie He; Quanting Yin; Hui Zhang; Mudan Yuan; Chunhua Yang; Geng Tian; Jia Mi; Fuyi Xu (npj Parkinson's Disease)
Abstract Magnetic resonance imaging and circulating molecular testing are potential methods for diagnosing and treating Parkinson’s disease (PD). However, their relationships remain insufficiently studied. Using genome-wide association summary statistics, we found in the general population a genetic negative correlation between white matter tract mean diffusivity and PD (-0.17 < Rg < -0.11, p < 0.05), and a positive correlation with intracellular volume fraction (0.12 < Rg < 0.2, p < 0.05). Additionally, 1345 circulating genes causally linked with white matter tract diffusivity were enriched for muscle physiological abnormalities (padj < 0.05). Notable genes, including LRRC37A4P (effect size = 15.7, p = 1.23E-55) and KANSL1-AS1 (effect size = -15.3, p = 1.13E-52), were directly associated with PD. Moreover, 23 genes were found linked with genetically correlated PD-IDP pairs (PPH4 > 0.8), including SH2B1 and TRIM10. Our study bridges the gap between molecular genetics, neuroimaging, and PD pathology, and suggests novel targets for diagnosis and treatment.